Adverse effects of imidocarb dipropionate (Imizol) in a dog - Abdullah, A. Salam; Abdul Rahman, Sheikh Omar; Desmond, Baggot J.; Saad, Mohd Zamri (Kluwer Academic Publishers, 1984)
One of 13 healthy dogs used in a pharmacokinetic study of imidocarb dipropionate died due to difficulty in breathing, tachycardia, weakness and profuse diarrhoea. Autopsy findings showed marked pulmonary congestion and oedema. Kidneys were grossly enlarged and markedly congested with extensive haemorrhage in the cortex and medulla. Marked tubulonephrosis was also exhibited microscopically. Liver and spleen were moderately enlarged and congested. The adverse effects of imidocarb may be due to excessive acetylcholine action.